Sex dimorphism of cortical water diffusion in normal aging measured by magnetic resonance imaging - Ng, Shu-Hang; Hsu, Wen-Chiun; Wai, Yau-Yau; Lee, Jiann-Der; Chan, Hsiao-Lung; Chen, YaoLiang; Fung, Hon-Chung; Wu, YihRu; Tsai, Ming-Lun; Wang, Jiun-Jie (Frontiers in Aging Neuroscience, 2013)
Background: The purpose of this study was to examine sex dimorphism in water diffusion in the brain throughout the normal aging process by magnetic resonance imaging. Methods: Diffusion-weighted images covering the majority of the brain were acquired from 77 healthy participants. Both the mean water diffusivity and diffusion kurtosis were calculated from the cortical regions and parcellated according to the template in anatomical automatic labeling. The mean water diffusivity and diffusion kurtosis from both sexes were examined and subsequently correlated with age. Statistical significance was set at a threshold of p < 0.01 after correction for multiple comparisons. In regions that reached statistical significance, a linear regression model was performed. Analysis of variance was conducted to determine the interaction between aging and sex. Results: Sex differences were observed for three aspects. First, compared to females, males presented increased mean water diffusivity and a decreased diffusion kurtosis in the frontal and temporal lobes. Second, a widespread age-related increase in mean water diffusivity was observed, which was more significant in the frontal, occipital, and temporal areas and in the cingulum in females. Third, the diffusion kurtosis decreased with aging but only in restricted areas for both sexes. For the interaction of aging and sex, the most significant change was observed with regards to mean diffusivity, mostly in the right amygdala. Conclusions: A sex-related dimorphism in water diffusion throughout the aging process was observed in the cortex using magnetic resonance imaging.